O lugar da intersubjetividade no Sistema do idealismo transcendental de Schelling - Cunha, João Geraldo Martins da (Discurso, 2021)
In this paper I intend to offer an interpretation to the “Second proposition” of practical philosophy — Chapter IV of the System of Transcendental Idealism (1800). From this textual delimitation my hypothesis is restricted to suggest that the relationship of reciprocal and indirect interaction between self-consciousnesses occupies a strategic “place” in Schelling's argument, since, it enables, at least initially, two problems to be solved: (1) the one concerning the contradiction rooted in the original limit of the transcendental acts of intelligence’s self-constitution as individual and free consciousness; and (2) the one regarding the articulation between theoretical and practical philosophy.